Pengaruh Pengetahuan dan Penerapan Perppu Nomor 1 Tahun 2017 tentang Akses Informasi Keuangan terhadap Kepatuhan Wajib Pajak (Studi Empiris Wajib Pajak Orang Pribadi di Cikarang Utara) - Khaerani Mahdinur Awlia; Whereson Siringoringo (President University Press, 2019)
The purpose of this study is to find out how much influence the knowledge and application of Perppu number 1 of 2017 about access to financial information on taxpayer compliance with individual taxpayers in North Cikarang. Research data obtained through questionnaires distributed to registered taxpayers and have NPWP in North Cikarang as many as 105 samples, sampling is done by non probality sampling, and data analysis method used is multiple linear regeresi analysis. The result of this research concludes that Knowledge of Perppu number 1 year 2017 about access of financial information have positive and significant influence to taxpayer compliance (value at t count 2,354> value at t table 1,983) application of Perppu number 1 year 2017 about access of financial information have influence positive and significant to taxpayer compliance (value at t count of 4.528> value at t table 1,983) and tested simultaneously Knowledge and Application of Perppu number 1 year 2017 about access of financial information positive and significant to tax compliance (F count 17,54> 3.08).